Analisis Implementasi Pembelajaran Active Learning di Kelas 4 SDN Blumbungan 3 Pamekasan - Farhanah, Nailah; Maula, Qurrotu Inayati (JOURNAL OF EDUCATION FOR ALL, 2024)
Learning will, of course, undergo a process of renewal in order to adapt to the demands of current developments, such as the curriculum update carried out by the government in recent years, namely the Merdeka Curriculum. In the Merdeka curriculum, students are required to always be active in the learning process and give teachers the freedom to use any model or method according to the needs of each student. When conducting research. The aim of this research is to find out whether there is an implementation of active learning in class 4 of SDN Blumbungan 3 Pamekasan. This research uses a descriptive qualitative method, which is an approach that states certain social situations by describing reality correctly in the form of words based on data collection and analysis techniques. relevant information obtained from natural situations involving teachers and students. The descriptive method is a method that examines a group of people, objects, conditions, thought systems, or current events. The descriptive qualitative research technique analyzes the implementation of active learning, namely by conducting observations, interviews, and documentation. The results found in class 4 at SDN Blumbungan 3 did not implement active learning because the teacher still used a lecture, discussion, and question-and-answer system in the learning process.